Urgensi Urgensi Pembuatan Perjanjian Tertulis sebagai Wujud Perlindungan Hukum Bagi Pelaku Arisan Online - Andreas Andrie Djatmiko; Dinar Ayu Marta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Advances in digital technology have brought significant changes to various aspects of life, including socio-economic activities such as arisan (social gathering). Arisan, which was previously conducted conventionally, has now begun to transform into online arisan. This change offers several advantages, including ease of access, reduced time constraints, and a wider range of participation. However, behind this convenience, an equally important challenge lies the lack of regulation and oversight of online arisan practices, which are prone to legal threats. This study aims to examine the urgency of creating written agreements in the implementation of online arisan and examine their legal force as a form of legal protection for the actors, both organizers and members. Using a normative juridical method through a regulatory-statutory approach and case studies, this study emphasizes the importance of legal validity in civil relations formed through online arisan. Data were obtained through observation, interviews, and documentation, which were then analyzed through a process of data reduction, presentation, and drawing conclusions. The results of the study indicate that written agreements in online arisan have legally binding force as long as they meet the requirements for a valid agreement according to Article 1320 of the Civil Code. The existence of a written agreement can increase legal certainty, strengthen the legal standing of the parties, and serve as valid evidence in the event of a breach of contract. Therefore, creating a written agreement is crucial to avoid losses and strengthen legal protection in online arisan (social savings and credit) practices. Furthermore, a written agreement also reflects the good faith of the parties in carrying out their commitments professionally and responsibly. This serves as an important foundation for building trust and creating a transparent and accountable online arisan system. Therefore, it is recommended that every online arisan participant create a clear written agreement and have it notarized to strengthen its legality.